Assessment of BioPattern in Novel Idea Generation for Bio-Inspired Design - Foo, Chin Toong; Omar, Badrul; Jalil, Azlis Sani (International Journal of Integrated Engineering, 2021)
BioPattern is a novel ideation tool for Bio-Inspired Design, built based on TRIZ, SAPPhIRE, and pattern language. It consists of an ontology, known as pattern-based ontology, and a sustainability evaluation, known as Ideal Windows. However, this framework has not been tested yet. Therefore, this article is to present the results and analysis of the case study conducted to assess this biomimicry framework. Two different groups of students, Creative & Innovation class (controlled group) and Integrated Engineering Design class (experimental group), are asked to generate innovative ideas where the experimental group employed BioPattern as the ideation tool. It is found that the level of innovation for the inventive ideas generated by the experimental group is much higher compared to that of the controlled group. Based on the inventive ideas produced by the experimental group, BioPattern is found to be efficient in ideation, able to generate effective solution, the problem-solution pairs of the ontology are adequate, and the biological solutions suggested are transferable as technological solutions. It can be concluded that BioPattern is able to bridge the biology-engineering gap.